Recognizing the Early Symptoms of Covid-19 Disease for Residents in the Work Area of the Health Center Banjarmasin City - Anita Agustina; Rohni Taufika Sari; Dessy Hadrianti; Zaqyyah Huzaifah (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2021)
The inability to recognize and know the early symptoms of the Covid-19 disease is one of the factors that increases the morbidity rate due to Covid-19. The most common symptoms of COVID-19 are fever, fatigue, and a dry cough. Some infected people do not show any symptoms and still feel well. Most (about 80%) of infected people recover without the need for special treatment. Based on this, it is necessary to disseminate correct information to all levels of society regarding the early symptoms of the Covid-19 disease and proper management. The purpose of this PKM activity is to provide health information about recognizing the early symptoms of the Covid-19 disease. The method used is Health Counseling to the community using Audio Visual Aid (AVA). The total audience is 39 people. The results of this PKM activity show that the audience listens and understands the information conveyed. Evaluation of the success of the activity showed that 73% of the total audience stated that they were very satisfied with the PKM activity, 90% of the audience understood the information provided. The conclusion of this activity shows that the community has high enthusiasm to recognize the symptoms and proper management of Covid-19 disease. Health workers and whole professions in the health sector are expected to be able to continue to monitor public to have the right knowledge and be able to do things in accordance with health protocols to reduce morbidity due to Covid-19 disease